Pengaruh Kualitas Pelayanan Dan Brand Image Terhadap Minat Beli Jasa PT Pos Indonesia - Yayu Rahayu (Public Service and Governance Journal, 2023)
This study aims to determine the effect of service quality and brand image on interest in buying services. The object of this research is the customer of PT Pos Indonesia Sekejati Bandung. Researchers conducted research with survey methods, namely data collection by distributing questionnaires. The researcher concludes that this study aims to test the established hypothesis, namely how much influence the independent variables, namely service quality and brand image have, then the dependent variable is interest in buying services. This research was conducted on 100 respondents using a quantitative approach. Analysis of the data used is regression analysis which is processed with the SPSS 26 application. The sampling technique in this study uses a non-probability sampling method with a purposive side technique that is with a specific purpose. The results of this study indicate that the description of the variables of service quality, brand image, and interest in buying services is included in the good category. Then by t test (partial) there is a significant influence between service quality on interest in buying services, and brand image on interest in buying services. as well as the f test (simultaneously) the two independent variables, service quality and brand image have a concurrent effect on the dependent variable of interest in buying services.